Assessing the Effects of Climate and Socioeconomic Factors on Vulnerability to Vector-Borne Diseases in Latin America - Rodrigo García Ayala; Andrés Estrugo (Inter-American Development Bank (IDB), 2014)
Climate change is imposing a large burden on the most vulnerable populations, particularly in the developing world. Establishing consistent causal relationships, however, is difficult because a multiplicity of climatic, economic and sociodemographic elements are combined to create the conditions for an outbreak of vector-borne disease. Based on a two-step procedure, this paper presents and tests an approach to estimating the effects of epidemic outbreaks on health vulnerability. The model proposed is empirically tested for five countries in Latin America where dengue is a national health priority. Using data from national censuses, satellite climate information and data from a newly developed disease outbreak surveillance online platform, the paper finds that climate has nonnegligible effects on health vulnerability. The evidence found and the vulnerability index constructed can be used to analyze the main determinants of vulnerability in order to address policy concerns.
hdl:11319/6567
Keywords: D04; Q51; Q54; R58; 330; Vulnerability; Climate change; Socioeconomic conditions; Vectorborne diseases; Factor analysis